2012
DOI: 10.1155/2012/245385
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Medulloblastoma in Childhood: Chang's Classification Revisited

Abstract: Purpose. To correlate the radiological aspects of metastases, the response to chemotherapy, and patient outcome in disseminated childhood medulloblastoma. Patients and Methods. This population-based study concerned 117 newly diagnosed children with disseminated medulloblastoma treated at the Institute Gustave Roussy between 1988 and 2008. Metastatic disease was assessed using the Chang staging system, their form (positive cerebrospinal fluid (CSF), nodular or laminar), and their extension (positive cerebrospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 24 publications
0
35
0
2
Order By: Relevance
“…This improvement indeed depends on advanced treatment strategies, such as the mega voltage radiation therapy and the adjuvant chemotherapy for high-risk patients. Unfortunately, many surviving patients suffer from therapy-related side effects, such as major neurocognitive impairment, hormonal and neurological deficits, obesity and increased risk of developing secondary tumors [3]. Therefore, it is necessary to recognize molecular abnormalities and distinct clinical behaviours of medulloblastoma patients in order to identify novel prognostic markers allowing the selection of patients requiring less intensive therapy, and to develop effective treatment strategies for the increase of high-risk patients' survival and for the decrease of therapy-related side effects.…”
Section: Introductionmentioning
confidence: 99%
“…This improvement indeed depends on advanced treatment strategies, such as the mega voltage radiation therapy and the adjuvant chemotherapy for high-risk patients. Unfortunately, many surviving patients suffer from therapy-related side effects, such as major neurocognitive impairment, hormonal and neurological deficits, obesity and increased risk of developing secondary tumors [3]. Therefore, it is necessary to recognize molecular abnormalities and distinct clinical behaviours of medulloblastoma patients in order to identify novel prognostic markers allowing the selection of patients requiring less intensive therapy, and to develop effective treatment strategies for the increase of high-risk patients' survival and for the decrease of therapy-related side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Despite medulloblastoma's high malignant potential, the development of extraneural metastases remains is uncommon. A study by Dufour et al [7] of 117 consecutive children with newly diagnosed disseminated medulloblastoma over a 20 year period described stage M3 (n ¼ 70) as more common than M2 (n ¼ 25) and stage M1 (n ¼ 22) disease but found no M4 disease. In 2010, Mazloom et al [8] reported a meta-analysis of 47 articles and 119 patients, with a median patient cohort of n ¼ 1 (max, n ¼ 8) per article and a median publication year of 1983 (range, 1961-2007).…”
Section: Discussionmentioning
confidence: 99%
“…Other common toxicity criteria (CTC) 4.0 grade 3 or 4 toxicities were also recorded . Response at the end of each stage of treatment was classified as complete response (CR), partial response (PR), stable disease (SD), or progressive disease (PD) . Anonymized scan and CSF results were returned with the questionnaire.…”
Section: Methodsmentioning
confidence: 99%